1978
DOI: 10.1002/pen.760181205
|View full text |Cite
|
Sign up to set email alerts
|

The effect of additives on the crystallization of poly (butylene terephthalate)

Abstract: The effect of glass fibers and some fire retardant additives on the kinetics and mechanism of crystallization of poly(butylene terephthalate) (PBT) has been investigated. Shorter half times of crystallization and higher optimum crystallization temperatures of the filled samples are attributed to the nucleating ability of the additives. Based on the percent crystallinity determined, the efficiency of the different quenching media studied can be arranged in the order: ice water > 25°C water ⩾ dry ice/ethanol > l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Equal parts of the 0.1% CNF suspension and 2% PBT solution were then mixed at 150-160 C under continuous magnetic stirring for 1 h. The resulting mixture was slowly cooled down to [30][31][32][33][34][35][36][37][38][39][40] C, after which a few drops of the mixture were placed between glass slides and maintained at this temperature for 24 h. The formed crystals were analyzed under polarized light using a Nikon OPTIPHOT-POL2 optical microscope. To further understand the morphology, the crystallized CNF-PBT solution (prepared by mixing equal parts of 0.1% CNF suspension and 2% PBT solution in o-chlorophenol) was filtered and washed repeatedly with methanol, followed by overnight drying in vacuum oven at 50…”
Section: Solution Crystallization Of Pbt and Cnf-pbt Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal parts of the 0.1% CNF suspension and 2% PBT solution were then mixed at 150-160 C under continuous magnetic stirring for 1 h. The resulting mixture was slowly cooled down to [30][31][32][33][34][35][36][37][38][39][40] C, after which a few drops of the mixture were placed between glass slides and maintained at this temperature for 24 h. The formed crystals were analyzed under polarized light using a Nikon OPTIPHOT-POL2 optical microscope. To further understand the morphology, the crystallized CNF-PBT solution (prepared by mixing equal parts of 0.1% CNF suspension and 2% PBT solution in o-chlorophenol) was filtered and washed repeatedly with methanol, followed by overnight drying in vacuum oven at 50…”
Section: Solution Crystallization Of Pbt and Cnf-pbt Samplesmentioning
confidence: 99%
“…40 The crystal sizes of PBT were observed to decrease because of the incorporation of glass fibers into the polymer solution. Park et al 41 have also studied the crystallization kinetics as well as nucleation effects of high loadings of glass fibers (30 wt %, 10 lm diameter, approximately 300 lm in length) in PBT dissolved in 10% TFA-CCl 4 (10% trifluoro acetic acid-carbon tetrachloride solution) and found that the filler particles led to an increase of the rate of crystallization.…”
mentioning
confidence: 99%
“…29 The observed crystallization behavior shows the effect of MWNTs on the crystallization kinetics of PBT under quiescent conditions, and the behavior is consistent with the reports in the literature. 3,6,8,9 In particular, the values shown in Table 1 confirm that the addition of MWNTs to the PBT produces an increase in the crystallization temperature T c . Similar results have been found by others as well.…”
Section: Effect Of Applied Shear On Nanocomposite Rheologymentioning
confidence: 54%
“…MWNTs were purchased from Sunnano (China). As reported by the manufacturer, the diameter of the MWNTs was 10-30 nm, and the average bulk density was 1.5 g/cm 3 .…”
Section: Experimental Materialsmentioning
confidence: 64%
See 1 more Smart Citation